Like a dark rabbi : modern poetry & the Jewish literary imagination - Finkelstein, Norman, 1954- (Hebrew Union College Press, 2019)
"Wallace Stevens' "dark rabbi," from his poem "Le Monocle de Mon Oncle," provides a title for this collection of essays on the "lordly study" of modern Jewish poetry in English. Including chapters on such poets as Charles Reznikoff, Allen Grossman, Chana Bloch, and Michael Heller, this volume explores the tensions between religious and secular worldviews in recent Jewish poetry, the often conflicted linguistic and cultural matrix from which this poetry arises, and the complicated ways in which Jewish tradition shapes the sensibilities of not only Jewish, but also non-Jewish, poets. Finkelstein, described as "one of American poetry's indispensible makers" (Lawrence Joseph), whose previous critical work has been called "the exemplary study of the religious aspect of the works of contemporary American poets" (Peter O'Leary), considers large literary and cultural trends while never losing sight of the particular formal powers of individual poems. In Like a Dark Rabbi, he offers a passionate argument for the importance of Jewish-American poetry to modern Jewish culture, and to American poetry more broadly, as it engages with the contradictions of contemporary life."--